Analisis Faktor-Faktor yang Memengaruhi Niat Penggunaan E-Commerce XYZ Menggunakan Model UTAUT (Unified Theory Acceptance and Use Of Technology) - Rizki Nanda Mustaqim; Ari Kusyanti; Himawat Aryadita (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The development of e-commerce in Indonesia more and more popular among the community. This is driven by the growing number of companies that provide businesses for e-commerce services to consumers (the business of electronic transactions between companies and consumers as buyers). XYZ E-commerce is one of the e-commerce in the field of popular fashion among teenagers. Model Unified Theory Acceptance And Use Of Technology (UTAUT) is a model that shows the factors that can affect the intention to use a particular technology (e-commerce). This research proposes 3 core variables of UTAUT model, that is performance expectancy, effort expectancy, social influence, which will be influenced to intention dependent variable or behavioral intention. The model was obtained from previous research. Data analysis technique is done by using multiple linear regression analysis. The result of this research is only social influence factor that influence to one's intention in using XYZ e-commerce, while the factor of expectancy and effort expectancy do not have significant influence toward behavioral intention.